ПРОЕКТУВАННЯ ОСВІТНЬОЇ КРАУДФАНДИНГОВОЇ ПЛАТФОРМИ ЗДОБУВАЧІВ ВИЩОЇ ОСВІТИ АГРАРНОГО ПРОФІЛЮ, В КОНТЕКСТІ ФОРМУВАННЯ БІЗНЕС КОМПЕТЕНТНОСТЕЙ - Альона Нєлєпова (International Journal of Innovative Technologies in Social Science, 2019)
The article discusses some aspects of crowdfunding platforms. has been explored the relevance of creating a crowdfunding platform and introducing it into the educational process with the purpose of forming business competencies. This research focuses on student projects. The purpose of creating a student crowdfunding platform is to integrate higher education applicants into project teams, to bring innovative products to the market at the facilities of universities and enterprises, to conduct research in one or another area.The research examines the mechanisms of crowdfunding as a structural unit of the e-environment for the formation of business competencies in universities of agricultural profile. The basic principles of crowdfunding platform functioning as a system of training creation and implementation of startup projects are considered, researched the global crowdfunding platform market. The structural elements as well as the architecture of the crowdfunding platform for forming business competencies in agrarian universities are identified. Structural elements of the interface of crowdfunding platforms and platforms of the CIS countries are investigated. The architecture and organizational infrastructure, technological components of the crowdfunding platform were designed to create, promote and commercialize innovative projects.